Physical Activity Level and Motor Aptitude: Motor Domains and Identification Capacity of Brazilian Insufficiently Active Older Adults - Andreis, Lucia M.; de Aguiar Lemos, Fernando; de Lima Silva, Lorenna W.; Garcia, Cassiana L. P.; Veras, Gabrielli; Neto, Francisco R. (Current Aging Science, 2021)
Background: A decrease in the physical activity level in old age is common, which results in an increase in the number of falls and chronic conditions. Associated with that occurs the decline in motor skills as a result of the deficit in the interaction of cognitive and motor processes. Physical activity levels can be associated differently with each motor domain. Objective: We analyzed the relationship between physical activity level and motor aptitude and to identify which motor domains were most sensitive to detect insufficiently active level in older adults. Methods: 385 elderly people of both sexes participated in the study. For the evaluation of the subjects, the International Questionnaire on Physical Activity and the Motor Scale for Older Adults were adopted. Results: The majority of the elderly were active. In comparing motor aptitude between active and insufficiently active (IAC) elders a significant difference was found in the Global Coordination, Balance, Body Scheme and General Motor Aptitude. From the analysis of the Area Under the Curve (AUC), we verified that these domains also were the ones that presented adequate diagnostic accuracy to identify IAC elderly. Besides that, active elderly have presented the General Motor Aptitude classified within normality while the IAC below the normal. Conclusion: Our data suggest that IAC older adults present lower motor aptitude than the active elderly, especially in the domains of Global Coordination, Balance, Body Scheme and General Motor Aptitude, and that these domains were sensitive to indicate IAC older adults.
Keywords: ROC curve